A shot in the dark? Policy influence on cluster networks - Holger Graf; Tom Brökel (Friedrich Schiller University Jena, 2019)
Cluster policies are often intended and designed to promote interaction in R&D among colocated organisations, as local knowledge interactions are perceived to be underdeveloped. In contrast to the popularity of the policy measure little is known about its impact on knowledge networks, because most scientific evaluations focus on impacts at the firm level. Using the example of the BioRegio contest, we explore cluster policy effects on local patent co-application and co-invention networks observed from 1985 to 2013, in 13 German regions. We find that the initiative increases network size and innovation activities during the funding period but not afterwards. The impact of the BioRegio contest on network cohesion is moderate. In contrast, general project-based R&D subsidisation is found to support cohesion more robustly.
Keywords: O31; Z13; 330; Cluster Policy; Knowledge Networks; Network Analysis; Patent Data; Regional Innovation; Policy Evaluation